KAJIAN ETIKA KRISTEN TERKAIT PERAN GURU DALAM MENERAPKAN PENDIDIKAN KARAKTER UNTUK MENGATASI KEMEROSOTAN KARAKTER SISWA DI ERA DIGITAL [A STUDY OF CHRISTIAN ETHICS RELATED TO THE TEACHER'S ROLE IN IMPLEMENTING CHARACTER EDUCATION TO OVERCOME CHARACTER DECLINE IN THE DIGITAL ERA] - Bora, Merliana Ina; Irawati, Wahyu (JOHME: Journal of Holistic Mathematics Education, 2022)
The digital era is synonymous with the use of technology that is beneficial for education. The use of technology must be balanced with character education to provide direction to students in utilizing technology. The decline in character in the digital era is evidence that character education has not been implemented optimally so that students deviate from the use of technology and internet networks. Teachers play an important role in overcoming character decline by instilling character values based on Christian ethics based on the Bible. Christian ethics is the basis for providing character education in the digital era. The purpose of this study was to determine the teacher's role in implementing character education to overcome the decline in student character in the digital era which was reviewed based on the study of Christian ethics. The method used is a literature review, namely a description of reading materials that are relevant to the research topic. Based on the literature review that has been carried out, it can be concluded that teachers have an important role in implementing character education to overcome the decline in student character in the digital era. The teacher has a role as an agent of reconciliation who guides students to have a Christ-like character with the aim of developing a Christian mindset, social responsibility, mental, physical, and social health and preparing students for the world of work.BAHASA INDONESIA ABSTRACT: Era digital identik dengan penggunaan teknologi yang bermanfaat bagi pendidikan. Penggunaan teknologi harus diimbangi dengan pendidikan karakter untuk memberikan arahan kepada siswa dalam memanfaatkan teknologi. Kemerosotan karakter di era digital adalah bukti pendidikan karakter belum dilaksanakan secara maksimal sehingga siswa melakukan penyimpangan terhadap penggunaan teknologi dan jaringan internet. Guru berperan penting untuk mengatasi kemerosotan karakter dengan menanamkan nilai-nilai karakter berdasarkan etika Kristen yang berlandaskan pada Alkitab. Etika Kristen merupakan dasar dalam memberikan pendidikan karakter di era digital. Tujuan penelitian ini adalah untuk mengetahui peran guru dalam menerapkan pendidikan karakter untuk mengatasi kemerosotan karakter siswa di era digital yang ditinjau berdasarkan kajian etika Kristen. Metode yang digunakan adalah kajian literatur yaitu deskripsi mengenai bahan-bahan bacaan yang relevan dengan topik penelitian. Berdasarkan kajian literatur yang telah dilakukan, dapat disimpulkan bahwa guru memiliki peran yang penting dalam menerapkan pendidikan karakter untuk mengatasi kemerosotan karakter siswa pada era digital. Guru memiliki peran sebagai agen rekonsiliasi yang menuntun siswa untuk dapat memiliki karakter serupa Kristus dengan tujuan mengembangkan pola pikir Kristen, tanggung jawab sosial, kesehatan mental, fisik, dan sosial serta mempersiapkan siswa untuk dunia kerja.